A continuous synthesis method of high-entropy oxide with controllable crystal form, components and proportions

Through continuous injection and high-throughput rapid annealing treatment, the problems of long processing time, complex process and inability to achieve rapid continuous production in the existing high-entropy oxide synthesis methods are solved, and the rapid synthesis of high-entropy oxides of various crystal forms, components and proportions are achieved, and the synthesis efficiency and yield are improved.

CN118771313BActive Publication Date: 2025-03-21ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410813799.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-03-21
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The existing high-entropy oxide synthesis methods have a long processing time, a complex process flow, and are unable to achieve rapid and continuous production, and it is difficult to achieve the controllable synthesis of high-entropy oxides of different crystal forms, components, and proportions at the same time.

Method used

The soluble metal salt aqueous solution, subcritical water and additives were mixed with hydrolysis reaction by continuous injection to obtain a high-entropy oxide precursor, and the high-throughput treatment was performed to achieve rapid synthesis of high-entropy oxides.

Benefits of technology

The rapid and continuous batch preparation of high-entropy oxides is achieved, and can be widely used in the synthesis of various high-entropy oxides with different crystal forms, components and proportions, improving the synthesis efficiency and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771313B_ABST
    Figure CN118771313B_ABST
Patent Text Reader

Abstract

The present invention provides a continuous synthesis method of a high-entropy oxide with controllable crystal form, components and proportions, and belongs to the technical field of inorganic materials. The present invention adopts a subcritical water mixing process and a rapid annealing process, and the synthesis method is simple and easy to implement, and can realize the rapid synthesis of high-entropy oxides, greatly improving the synthesis efficiency of high-entropy oxides; the present invention can adopt a preparation method of continuous sampling + high-throughput processing, and can quickly realize the uninterrupted continuous production of different high-entropy oxides, which is conducive to industrial batch production; the present invention can be applied to the controllable synthesis of a variety of high-entropy oxides with different crystal forms, different element components, and different element proportions, and has a wide range of applicability, which is conducive to the testing and development of different high-entropy oxides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic materials, and in particular to a continuous synthesis method of high-entropy oxides with controllable crystal form, components and proportions. Background Art

[0002] High entropy oxides (HEOs) are emerging materials first proposed in 2015. They are generally composed of five or more metal cations uniformly distributed in a single-phase oxide structure in a near-equimolar ratio to form a stable solid solution. Compared with conventional doped oxides, the mixing entropy of HEOs plays a dominant role in the preparation and formation process, which leads to a more disordered chemical structure and atomic distribution, resulting in unique thermodynamic, reaction kinetic, and crystal structure characteristics: (1) The severe lattice distortion commonly found in HEOs increases the number of oxygen vacancies and activates lattice oxygen, which is beneficial to the improvement of multiple performance properties of the material; (2) The "hysteresis diffusion effect" of this type of material can effectively prevent the agglomeration of various elements during the reaction process, improving the thermal stability at high temperatures; (3) The numerous optional constituent elements make it possible to customize the preparation of HEOs, thus having a "cocktail effect". Based on these characteristics, HEOs have currently demonstrated excellent performance in catalysis, optics, energy storage, magnetism, electrochemistry, and other fields.

[0003] Thanks to the rich composition of optional elements and the high inclusiveness of high-entropy structures, the theoretical number of high-entropy oxides is 3 to 4 orders of magnitude higher than that of conventional oxide materials. In the initial stages of research, researchers have already synthesized hundreds of different high-entropy oxide materials, mainly in the form of rock salt, spinel, fluorite, perovskite, and pyrochlore, covering almost all alkali metals, alkaline earth metals, rare earth metals, and transition metal elements. The existing methods for synthesizing high entropy oxides mainly include ball milling, co-precipitation, template method, vapor deposition method, high-energy ultrasonic method, etc. However, these synthesis methods generally have the following problems: (1) They require long processing time or complex process flow. Such harsh reaction conditions lead to slow synthesis speed and lack the potential for industrial production; (2) They mostly adopt intermittent one-pot preparation process, which cannot achieve rapid switching between different samples and is difficult to prepare continuously in batches. Therefore, the output of high entropy oxides is severely limited; (3) The synthesis methods are basically only targeted at one or several high entropy oxide products of the same type, lack universality, and it is difficult to simultaneously achieve the controllable synthesis of high entropy oxides with different crystal forms, different elemental components, and different element ratios, thereby greatly increasing the cost of material development and research.

[0004] Chinese patent publication number CN110204328 discloses a method for preparing high-entropy oxide ceramics. The method can selectively mix four or five of the metal oxides MgO, ZnO, NiO, CuO, CaO, CoO, ZrO2, CeO2, Al2O3, Gd2O3, La2O3, Er2O3, Y2O3, Fe2O3, Co3O4, and CaCO3 to form a high-entropy oxide ceramic with a single crystal structure. However, the patent has the following problems: (1) only partial adjustment of the type of metal element is achieved, but the molar ratio of the metal atoms still needs to be maintained at 1:1:1:1 or 1:1:1:1:1; (2) the ball milling and heat treatment steps in the preparation process are too long, all exceeding 10 hours, making it impossible to achieve rapid and continuous production, which seriously limits production efficiency. Chinese Patent Publication No. CN113621988 discloses a highly efficient oxygen evolution high-entropy amorphous oxide nanocatalyst, its preparation method, and applications. The metal elements in the catalyst described in this patent can be composed of any five or more of the following: Fe, Co, Ni, Mn, Cu, Sn, Sb, Cr, Ru, and Ir, with the atomic concentration of each metal atom ranging from 5% to 60%. This patent achieves controlled synthesis of the composition and ratio of the metal elements in the high-entropy oxide material. However, the high-entropy oxides prepared using a reduction method all have an amorphous structure, making it impossible to control different crystalline structures, limiting their applications in optical, energy storage, and magnetic fields. Chinese Patent Publication No. CN115000387 discloses a method for preparing a spinel-type TM-HEO / C composite material. The microwave heating method described in this patent achieves the synthesis of the TM-HEO / C composite material in just 0.5-5 minutes. This preparation method is simple, fast, energy-efficient, and low-cost, facilitating rapid and large-scale production of high-entropy oxides. However, the high-entropy oxide synthesized in this patent is limited to the spinel crystal form, and the optional metal elements are limited to transition metals such as Cr, Mn, Fe, Co, Ni, Cu, and Zn. There is still room for improvement in the versatility of the synthesis technology.

[0005] Therefore, developing a synthesis method that can take into account continuous preparation, rapid production, and be widely used in various high-entropy oxides with different crystal forms, components, and proportions is of great significance for the research, screening, and industrial application of such inorganic materials. Summary of the Invention

[0006] The object of the present invention is to provide a continuous synthesis method of high-entropy oxides with controllable crystal forms, components and proportions. The synthesis method is simple and easy to implement, the process flow can be carried out continuously in batches, and the controllable synthesis of multiple high-entropy oxides with different crystal forms, components and proportions can be achieved quickly.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a continuous synthesis method of a high-entropy oxide with controllable crystal form, components and proportions, comprising the following steps:

[0009] A continuous sampling method is used to mix a soluble metal salt aqueous solution, subcritical water and an additive, and a hydrolysis reaction is carried out to obtain a high entropy oxide precursor;

[0010] A high-entropy oxide precursor is subjected to a rapid annealing treatment using a high-throughput processing method to obtain a high-entropy oxide;

[0011] The types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides of the same crystal form and the same elemental composition;

[0012] Or the types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides of the same crystal form and different elemental compositions;

[0013] Or the types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides with different crystal forms and different elemental compositions;

[0014] The auxiliary agent includes an acid, a base or an oxidizing agent;

[0015] The heating rate of the rapid annealing process is greater than 80° C. / s.

[0016] Preferably, the concentration of each metal ion in the soluble metal salt aqueous solution is independently 0.001 to 1 mol / L.

[0017] Preferably, the acid includes nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid or oxalic acid, the base includes ammonia water, sodium hydroxide or potassium hydroxide, the oxidant includes hydrogen peroxide, percarbonate or persulfate, and the concentration of the auxiliary agent is 0.1 to 10 mol / L.

[0018] Preferably, the volume ratio of the soluble metal salt aqueous solution, subcritical water and additive is 1:2-5:0.1-1.

[0019] Preferably, the mixing temperature is 200-370° C., and the pressure is 15-22 MPa; and the hydrolysis reaction time is 2-30 seconds.

[0020] Preferably, the temperature of the rapid annealing treatment is 500-1400° C., and the holding time is 10-300 s; and the carrier gas of the rapid annealing treatment includes 5-100% O 2 and the balance N 2 in terms of volume fraction.

[0021] Preferably, the high entropy oxide includes one or more of rock salt crystal type high entropy oxide, spinel crystal type high entropy oxide, fluorite crystal type high entropy oxide, perovskite crystal type high entropy oxide and pyrochlore crystal type high entropy oxide.

[0022] Preferably, the chemical formula of the rock salt crystal high entropy oxide is The lattice space group is Fm-3m, and the metal element R N Including 5 to 8 of Li, Na, Mg, Cr, Mn, Co, Ni, Cu, Zn, and Ga; the atomic ratio of each metal element Xn=0.111 to 0.333 and

[0023]

[0024] The general chemical formula of the spinel crystal high entropy oxide is The lattice space group is Fd-3m, and the metal element S N Including 5 to 9 of Li, Mg, Ca, Sr, Ba, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn and Al; the atomic ratio of each metal element Xn = 0.100 to 0.333 and

[0025] The general chemical formula of the fluorite crystal type high entropy oxide is The lattice space group is Fm-3m or Ia-3m, and the metal element F N Including 5 to 9 of Y, Zr, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, and the atomic ratio of each metal element Xn=0.100 to 0.333 and

[0026] Preferably, the chemical formula of the perovskite-type high entropy oxide is The lattice space group is Pm-3m, A K A is the metal element contained in the A-site ion of the perovskite crystal high entropy oxide. K Including K species among Ca, Sr, Ba, Y, La, Pr, Nd, Sm and Gd, 1≤K≤6; B M is the metal element contained in the B-site ion, B M The invention comprises M kinds of Ti, Cr, Mn, Fe, Co, Ni, Zn and Zr, 1≤M≤6, N=K+M and 6≤N≤10, the atomic ratios of the metal elements Xk and Ym at the A position or B position are independently 0.143 to 1.000, and

[0027]

[0028] Preferably, the chemical formula of the pyrochlore crystal type high entropy oxide is The lattice space group is Fd-3m, C K It is the metal element contained in the C-site ion of the pyrochlore crystal high entropy oxide, C KIncluding K species among Y, La, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, 1≤A≤6; D M is the metal element contained in the D-site ion, D M The invention comprises M kinds of Ti, Sn, Cr, Mn, Fe, Co, Ni, Zr and Ir, 1≤B≤6, N=K+M and 6≤N≤10, the atomic ratios Xk and Ym of the metal elements at the C position or D position are independently 0.143 to 1.000, and

[0029] The present invention provides a continuous synthesis method of high-entropy oxides with controllable crystal form, components and proportions. In the present invention, a soluble metal salt aqueous solution is mixed with subcritical water, and the solubility of each metal ion in the solution is drastically reduced to form a supersaturated solution. + or OH - Under the influence of the species, a violent hydrolysis reaction occurs, nucleation explodes in the liquid to form homogeneous nanoparticles precipitated, and uniform mixing is achieved under the mass transfer effect of subcritical water while maintaining a small particle size at the nanometer level, which facilitates the subsequent annealing heat treatment process; then, the present invention controls the heating rate of the annealing treatment to be greater than 80°C / s, which can accelerate the reaction rate and shorten the annealing time. Only an annealing treatment time of less than 300s is required to form a single crystalline phase of high-entropy oxide, achieving rapid synthesis. However, the existing synthesis method cannot form a single phase under such a short annealing treatment time (Comparative Example 1).

[0030] In the method of the present invention, after the subcritical water hydrolysis reaction, heating is only required in the annealing stage, and no heating is required in other treatment stages, shortening the unnecessary heating time to avoid excessive growth and agglomeration of crystal particles. Therefore, the present invention adopts a rapid annealing process to effectively suppress the excessive growth and agglomeration segregation of high entropy oxide particles on the basis of minimum satisfaction of the thermodynamic formation energy barrier of high entropy oxide materials, and greatly shortens the synthesis time.

[0031] The subcritical water mixing process and rapid annealing process adopted in the present invention ensure that the samples do not interfere with each other during the synthesis process, and the various high-entropy oxide materials prepared have pure and complete structures.

[0032] The present invention adopts a continuous injection method to continuously introduce various different metal salt solutions and additives and react them with subcritical water, thereby sequentially and continuously preparing various different high-entropy oxide precursors; moreover, the continuous method has no limit on the total injection volume of each metal salt solution, and a large amount of solution can be continuously introduced to achieve large-scale production.

[0033] The present invention allows for rapid annealing of the prepared high-entropy oxide precursor using a high-throughput method, enabling simultaneous batch processing of multiple high-entropy oxide precursors with different crystal forms, compositions, and ratios. This allows for the rapid and simultaneous synthesis of high-entropy oxides with different crystal forms, compositions, and ratios. Furthermore, the high-entropy oxides produced by the synthesis method are structurally pure and complete, without interfering with each other. Furthermore, the high-throughput method imposes no upper limit on the number of samples that can be processed simultaneously, meeting the requirements of industrial mass production applications.

[0034] The synthesis method of the present invention is simple and easy, the reaction time of each step is short, and the rapid synthesis of high-entropy oxides can be achieved, which greatly improves the synthesis efficiency of high-entropy oxides. The present invention adopts a preparation method of continuous sampling + high-throughput processing, which can quickly achieve uninterrupted continuous production of different high-entropy oxides, which is conducive to industrial batch production. The present invention can be applied to the controllable synthesis of a variety of high-entropy oxides with different crystal forms, different elemental components, and different element ratios, has wide applicability, and is conducive to the testing and development of different high-entropy oxides. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a flow chart of the continuous synthesis method of the high-entropy oxide with controllable crystal form, components and proportions according to the present invention;

[0036] Figure 2 XRD spectra of rock salt crystal high entropy oxide RS-A and RS-A' prepared in Example 1 and Comparative Example 1;

[0037] Figure 3 EDS graphs of the metal atomic ratios of the rock salt crystal high entropy oxides RS-A and RS-A' prepared in Example 1 and Comparative Example 1;

[0038] Figure 4 TEM images of rock salt crystal high entropy oxide RS-A and RS-A' prepared in Example 1 and Comparative Example 1;

[0039] Figure 5 XRD spectra of the FL-A series of spinel high entropy oxides with different element ratios prepared in Example 2;

[0040] Figure 6 EDS graphs of metal atomic ratios of the spinel high entropy oxide FL-A series with different element ratios prepared in Example 2;

[0041] Figure 7 (a) XRD spectrum and (b) SAED single crystal diffraction spots of the perovskite high entropy oxide PE-A prepared in Example 3;

[0042] Figure 8This is an EDS graph of the metal atomic ratio of the perovskite-type high entropy oxide PE-A prepared in Example 3;

[0043] Figure 9 XRD spectra of fluorite-type high-entropy oxides FL-A, FL-B, and FL-C with different elemental compositions prepared in Example 4;

[0044] Figure 10 TEM images of fluorite-type high-entropy oxides FL-A, FL-B, and FL-C with different elemental compositions prepared in Example 4;

[0045] Figure 11 EDS-mapping distribution diagrams of the metal elements of fluorite-type high-entropy oxides FL-A, FL-B, and FL-C with different elemental compositions prepared in Example 4;

[0046] Figure 12 This is the XRD spectrum of the spinel high entropy oxide SP-B prepared in Example 5;

[0047] Figure 13 (a) EDS image of metal atomic ratio and (b) TEM image of the spinel high entropy oxide SP-B prepared in Example 5;

[0048] Figure 14 XRD spectra of different high entropy oxides RS-B, PE-B, and PY-A prepared in Example 6;

[0049] Figure 15 EDS diagram of the metal atomic ratio of different high entropy oxides RS-B, PE-B and PY-A prepared in Example 6. DETAILED DESCRIPTION

[0050] like Figure 1 As shown, the present invention provides a continuous synthesis method of a high-entropy oxide with controllable crystal form, composition and ratio, comprising the following steps:

[0051] A continuous sampling method is used to mix a soluble metal salt aqueous solution, subcritical water and an additive, and a hydrolysis reaction is carried out to obtain a high entropy oxide precursor;

[0052] A high-entropy oxide precursor is subjected to a rapid annealing treatment using a high-throughput processing method to obtain a high-entropy oxide;

[0053] The types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides of the same crystal form and the same elemental composition;

[0054] Or the types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides of the same crystal form and different elemental compositions;

[0055] Or the types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides with different crystal forms and different elemental compositions;

[0056] The auxiliary agent includes an acid, a base or an oxidizing agent;

[0057] The heating rate of the rapid annealing process is greater than 80° C. / s.

[0058] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0059] In the present invention, the concentration of each metal ion in the aqueous solution of the soluble metal salt is preferably independently 0.001 to 1 mol / L, more preferably 0.01 to 0.1 mol / L, and further preferably 0.02 to 0.05 mol / L.

[0060] The metal salts of the present invention preferably include nitrates, chlorides, sulfates, metal acid salts or organic metal salts of the corresponding metal elements. The present invention is not particularly limited to the specific types of different metal salts, and the corresponding water-soluble metal salts well known in the art can be used.

[0061] The type of metal salt required for the soluble metal salt of the present invention is preferably adjusted according to the crystal form and elemental composition of the high entropy oxide to be prepared.

[0062] In the present invention, the auxiliary agent includes an acid, an alkali or an oxidizing agent; the acid preferably includes nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid or oxalic acid, the alkali preferably includes ammonia water, sodium hydroxide or potassium hydroxide, and the oxidizing agent preferably includes hydrogen peroxide, percarbonate or persulfate; the percarbonate is preferably sodium percarbonate or potassium percarbonate, and the persulfate is preferably ammonium persulfate. The auxiliary agent is preferably used in the form of an aqueous solution; the concentration of the auxiliary agent is preferably 0.1 to 10 mol / L, more preferably 0.5 to 6 mol / L, and further preferably 1 to 2 mol / L.

[0063] The present invention utilizes auxiliary agent to provide more H for reaction system + or OH - The addition of a reducing or oxidizing agent to the reaction system can further accelerate the reaction and maintain the specific form or valence of certain metal elements in the system, ensuring the accurate synthesis of the target crystal form. In addition, the present invention controls the concentration of the auxiliary agent within an appropriate range to avoid excessively high auxiliary agent concentrations causing an overly rapid reaction and resulting in excessively large product particle size.

[0064] In the present invention, the subcritical water is water at a temperature of 200 to 370° C. and a pressure of 15 to 22 MPa. The present invention has no particular limitation on the source of the subcritical water, and the water can be obtained in a manner well known in the art.

[0065] In the present invention, the volume ratio of the soluble metal salt aqueous solution, subcritical water and auxiliary agent is preferably 1:2-5:0.1-1, more preferably 1:2-3:0.6-1.

[0066] In the present invention, the mixing temperature is preferably 200-370°C, more preferably 280-360°C, further preferably 310-350°C, and the pressure is preferably 15-22 MPa, more preferably 18-20 MPa; the hydrolysis reaction time is preferably 2-30 s, more preferably 5-20 s, further preferably 8-15 s.

[0067] In the present invention, the continuous sampling is preferably achieved in the form of continuous sampling by a high-pressure pump; the present invention preferably uses a high-pressure pump to simultaneously extract the soluble metal salt aqueous solution, subcritical water and auxiliary agent into the reactor for mixing; the extraction flow rate of the soluble metal salt aqueous solution is preferably 7.5 to 30 mL / min, more preferably 10 to 20 mL / min; the extraction flow rate of the subcritical water is preferably 20 to 90 mL / min, more preferably 40 to 50 mL / min, and the extraction flow rate of the auxiliary agent is preferably 1 to 30 mL / min, more preferably 7.5 to 10 mL / min.

[0068] In the present invention, when preparing different high entropy oxides, the present invention preferably configures an electrically controlled valve in the channel for introducing the metal salt solution to achieve seamless switching of the injection of different metal salt solutions. After each portion of the metal salt solution is injected, the next portion of the metal salt solution is switched in sequence, and the corresponding suspension products are collected separately to achieve continuous synthesis of different high entropy oxide samples. At the same time, when preparing different high entropy oxides, the present invention preferably adopts a high-throughput parallel method to filter and wash the different suspension products separately to obtain the corresponding different high entropy oxides.

[0069] The present invention mixes a soluble metal salt aqueous solution with subcritical water to prepare a high entropy oxide precursor. Subcritical water is water at a temperature of 200 to 370°C and a pressure of 15 to 22 MPa. In the present invention, subcritical water serves as both a solvent and a reactant: (1) As a solvent, the density and viscosity of subcritical water are significantly lower than those at room temperature and pressure, while the specific heat capacity increases sharply, which makes it have stronger mass transfer and heat transfer effects, greatly promoting the diffusion and migration of water molecules and solute molecules, thereby significantly improving the reaction rate and promoting the uniform mixing of multiple elements. (2) As a reactant, the dielectric constant of subcritical water decreases significantly, and a large number of hydrogen bonds in the water are destroyed, thereby reducing the solubility of the metal salt therein, causing the metal element solute therein to precipitate rapidly due to excessive supersaturation. At the same time, as the pressure and temperature gradually increase to the subcritical level, the ionic product of water decreases from 10 at room temperature to 10 at room temperature. -14 Increased to 10-7 , which ensures that there are more H + and OH - species, making it an ideal medium for acid-base reactions. In contrast, the ion product of supercritical water is only 10 -20 The present invention mixes the soluble metal salt aqueous solution with the subcritical water in this state, and the solubility of each metal ion in the solution decreases sharply, forming a supersaturated solution, and in the presence of a large amount of H + or OH - Under the influence of the species, a violent hydrolysis reaction occurs, and nucleation explodes in the liquid to form homogeneous nanoparticles precipitated. Under the mass transfer effect of subcritical water, uniform mixing is achieved and the small particle size of the nanometer level is maintained, which is convenient for subsequent heat treatment.

[0070] After the hydrolysis reaction is completed, the present invention preferably washes and dries the obtained product in sequence; the washing method preferably includes centrifugal washing, filter press washing, ultrasonic vibration washing or spray washing; the drying method preferably includes low-temperature drying in a blower, freeze vacuum drying or infrared irradiation drying; the present invention does not specifically limit the specific conditions of different washing and drying methods, and can be carried out according to conditions well known in the art.

[0071] The high-throughput processing method of the present invention preferably adopts high-throughput parallel rapid annealing processing; the present invention preferably controls the high-throughput parallel processing capacity according to actual processing requirements.

[0072] In the present invention, the heating rate of the rapid annealing treatment is >80°C / s, more preferably 87.5-120°C / s, and further preferably 90-100°C / s; the temperature of the rapid annealing treatment is preferably 500-1400°C, more preferably 800-1000°C, and further preferably 875-900°C; the holding time is preferably 10-300s, more preferably 20-120s, and further preferably 40-100s; in terms of volume fraction, the carrier gas of the rapid annealing treatment includes 5-100% O2, with the balance being N2.

[0073] For a multi-component system of high entropy oxides, the mixing Gibbs free energy ΔG of its preparation process is mix The expression for ΔG mix =ΔH mix -TΔS mix , where ΔH mix and ΔS mix are the fixed mixing enthalpy and mixing entropy of the system, and T is the controllable reaction temperature of the mixing process; only when the temperature T is raised to the point where ΔG mix T is a negative value mixWhen T>T mix Under the reaction conditions, a heterogeneous solid-phase reaction occurs inside the multi-component system, in which the diffusion kinetics of each component determines the heat treatment time t of the sample. Given that the particle size of the high-entropy oxide precursor after the subcritical water reaction is small and the elements are evenly distributed, this type of precursor system can achieve multi-component diffusion mixing in a shorter time t and quickly form a single-phase solid solution. Therefore, the rapid annealing process adopted in the present invention can enable the high-entropy oxide precursor to form a single-phase solid solution after a very short period of high-temperature heat treatment and ensure the stability of the crystal form. At the same time, the temperature is raised to T at a faster rate. mix The above temperature also avoids excessive agglomeration and growth of crystal particles; in addition, the introduction of a suitable gas atmosphere can prevent cross-contamination between samples and achieve rapid cooling.

[0074] In the present invention, the high entropy oxide preferably includes rock salt crystal type high entropy oxide, spinel crystal type high entropy oxide, fluorite crystal type high entropy oxide, perovskite crystal type high entropy oxide and pyrochlore crystal type. Among the high entropy oxides, the rock or salt crystal type is preferably selected. The general chemical formula of the high entropy oxide is The lattice space group is Fm-3m, and the metal element R N Preferably, the metals include 5 to 8 of Li, Na, Mg, Cr, Mn, Co, Ni, Cu, Zn, and Ga; the atomic ratio of each metal element is Xn = 0.111 to 0.333 and

[0075] In the present invention, the chemical formula of the spinel crystal high entropy oxide is The lattice space group is Fd-3m, and the metal element S N Preferably, the metals include 5 to 9 of Li, Mg, Ca, Sr, Ba, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn and Al; the atomic ratio of each metal element is Xn = 0.100 to 0.333 and

[0076] In the present invention, the chemical formula of the fluorite crystal type high entropy oxide is The lattice space group is Fm-3m or Ia-3m, and the metal element F N It preferably includes 5 to 9 of Y, Zr, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, and the atomic ratio of each metal element Xn=0.100 to 0.333 and

[0077] In the present invention, the chemical formula of the perovskite crystal high entropy oxide is The lattice space group is Pm-3m, A KA is the metal element contained in the A-site ion of the perovskite crystal high entropy oxide. K Including K species among Ca, Sr, Ba, Y, La, Pr, Nd, Sm and Gd, 1≤K≤6; B M is the metal element contained in the B-site ion, B M The invention comprises M kinds of Ti, Cr, Mn, Fe, Co, Ni, Zn and Zr, 1≤M≤6, N=K+M and 6≤N≤10, the atomic ratios Xk and Ym of the metal elements at the A position or B position are independently 0.143 to 1.000, the adjustment of the metals at the A position and the B position does not interfere with each other, and

[0078] In the present invention, the chemical formula of the pyrochlore crystal type high entropy oxide is The lattice space group is Fd-3m, C K It is the metal element contained in the C-site ion of the pyrochlore crystal high entropy oxide, C K Including K species among Y, La, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, 1≤K≤6; D M is the metal element contained in the D-site ion, D M Including M species among Ti, Sn, Cr, Mn, Fe, Co, Ni, Zr and Ir, 1≤M≤6, and N=K+M and 6≤N≤10, the atomic ratio of metal elements Xk and Ym at C or D position is independently 0.143~1.000, and the adjustment of C and D position metals does not interfere with each other and

[0079] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0080] Example 1

[0081] (1) Dissolve five soluble metal nitrates, Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2, in deionized water at a molar ratio of 1:1:1:1:1 to prepare 500 mL of solution A, where the concentration of each metal ion is 0.02 mol / L. Weigh NaOH and dissolve it in deionized water to prepare additive A, with a concentration of 2.0 mol / L, for a total of 500 mL.

[0082] (2) Using a high-pressure pump, solution A, subcritical water, and additive A were simultaneously drawn into the reactor in the form of continuous sampling. The extraction flow rates were 10 mL / min, 20 mL / min, and 10 mL / min, respectively. The reactor was maintained at 370°C and 19 MPa and operated continuously. After the three liquids were mixed and hydrolyzed in the reactor for 20 seconds, a precursor suspension was obtained. After continuous extraction for 50 minutes, a high-entropy oxide precursor RS-A suspension of 2 L was formed.

[0083] (3) The obtained RS-A suspension was hydraulically filtered and washed three times, dried using infrared irradiation, and then rapidly annealed at 875°C in an air atmosphere (20% O2 by volume, balance N2) with a heating rate of 87.5°C / s for 30 seconds. After cooling, 3.45 g of high entropy oxide was obtained, which was recorded as RS-A.

[0084] The product RS-A prepared in this example is a high entropy oxide (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O, has a typical rock salt crystal form, space group is Fm-3m, and no impurity phase is generated.

[0085] In the product RS-A prepared in this example, the five metal elements Mg, Co, Ni, Cu, and Zn are evenly mixed in the sample RS-A, and the element ratio is still maintained at 1:1:1:1:1 ( Figure 3 RS-A is a nanoparticle with a particle size distribution of 60-90nm ( Figure 4 ).

[0086] Comparative Example 1

[0087] (1) Prepare 500 mL each of solution A and additive A in the same manner as in Example 1;

[0088] (2) Using a peristaltic pump, solution A, deionized water, and additive A were simultaneously extracted in a continuous injection manner at flow rates of 10 mL / min, 20 mL / min, and 10 mL / min, respectively. The three liquids were mixed and reacted in the reactor at room temperature and pressure for 20 s to obtain a precursor suspension RS-A'. The extraction was continued for 50 min to form a total suspension of 2 L.

[0089] (3) The obtained suspension RS-A' was filtered and washed three times, dried by infrared irradiation, and then rapidly annealed at 875°C in an air atmosphere (20% O2 by volume, balance N2) with a heating rate of 87.5°C / s for 30 seconds. After cooling, 2.76 g of high entropy oxide was obtained, which was recorded as RS-A'.

[0090] The product RS-A' prepared in this comparative example is an oxide with a main body of rock salt crystal form, but there are obvious diffraction peaks of impurity phase ( Figure 2 ), the crystal structure is not a single phase.

[0091] The ratio of the five metal elements was determined to be 0.9:0.7:0.6:1:1. The content of Cu and Zn elements was significantly higher than that of the other three elements Mg, Co, and Ni. The uneven distribution of Cu element and the obvious segregation phenomenon were the reasons for the existence of the second phase in the crystal structure. The particle size distribution of RS-A' was 30~110nm ( Figures 3-4 ).

[0092] Example 2

[0093] (1) Dissolve five metal nitrates, Cr(NO3)3, Mn(NO3)2, Fe(NO3)3, Co(NO3)2, and Ni(NO3)2, in deionized water. Prepare 6 mixed metal salt aqueous solutions (100 mL each) at molar ratios of 1:1:1:1:1, 2:1:1:1:1, 1:2:1:1:1, 1:1:2:1:1, 1:1:1:2:1, and 1:1:1:1:2, respectively. These solutions are named SP-A-0, SP-A-1, SP-A-2, SP-A-3, SP-A-4, and SP-A-5, respectively. The total concentration of metal elements in each mixed metal salt aqueous solution is maintained at 0.06 mol / L. Measure NH3·H2O and dilute it with deionized water to prepare additive B with a concentration of 1.0 mol / L, totaling 60 mL.

[0094] (2) A high-pressure pump was used to simultaneously draw the SP-A-series metal salt solution, subcritical water, and additive B into the reactor in the form of continuous sampling. The extraction flow rates were 10 mL / min, 40 mL / min, and 1 mL / min, respectively. The channel of the metal salt solution was equipped with an electronically controlled valve to achieve seamless switching between the injections of each sample. The reactor was maintained at 310°C and 22 MPa and operated continuously. After the three liquids were mixed and hydrolyzed in the reactor for 15 seconds, a precursor suspension was obtained.

[0095] After each SP-A-solution injection, the next sample was sequentially switched for reaction. The corresponding suspension products were collected separately, arranged in order from 0 to 5, and named consistent with the solution. After continuous extraction of each liquid for a total of 60 minutes (10 minutes for each metal salt solution), 510 mL of each suspension of the high-entropy oxide precursors SP-A-0, SP-A-1, SP-A-2, SP-A-3, SP-A-4, and SP-A-5 were formed.

[0096] (3) Using a multi-channel high-speed centrifuge, six portions of SP-A series suspensions were washed three times at a speed of 10,000 r / min, and then dried at 110°C for 10 min. The dried products were subjected to high-throughput parallel rapid annealing at 900°C in a mixed atmosphere (5% O2 by volume, the balance being N2), with a heating rate of 90°C / s and a heat treatment time of 20 s. After cooling, six high-entropy oxides were obtained: SP-A-0, SP-A-1, SP-A-2, SP-A-3, SP-A-4 and SP-A-5, with respective weights of 0.45 g, 0.39 g, 0.42 g, 0.43 g, 0.43 g and 0.49 g, respectively.

[0097] The six products prepared in this example are all high entropy oxides with a single crystal structure, all of which are typical spinel crystals with a space group of Fd-3m and no impurity phases ( Figure 5 ).

[0098] The five elements Cr, Mn, Fe, Co, and Ni are evenly distributed in each sample, and the element ratio is consistent with the ratio set when the solution is prepared ( Figure 6 ), each sample is:

[0099] SP-A-0 is (Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 )3O4;

[0100] SP-A-1 is (Cr 0.332 Mn 0.167 Fe 0.167 Co 0.167 Ni 0.167 )3O4;

[0101] SP-A-2 is (Cr 0.167 Mn 0.332 Fe 0.167 Co 0.167 Ni 0.167 )3O4;

[0102] SP-A-3 is (Cr 0.167 Mn 0.167 Fe 0.332 Co 0.167 Ni 0.167 )3O4;

[0103] SP-A-4 is (Cr 0.167 Mn 0.167 Fe 0.167 Co 0.332 Ni 0.167)3O4;

[0104] SP-A-5 is (Cr 0.167 Mn 0.167 Fe 0.167 Co 0.167 Ni 0.332 )3O4.

[0105] Example 3

[0106] (1) Six soluble metal salts, La(NO3)3, Cr(NO3)3, Mn(NO3)2, Fe(NO3)3, Co(NO3)2, and Ni(NO3)2, were dissolved in deionized water at a molar ratio of 5:1:1:1:1:1 to prepare 5 L of solution C, in which the total concentration of metal ions was maintained at 0.1 mol / L; NaOH and H2O2 were measured and dissolved in deionized water to prepare auxiliary agent C, totaling 2.5 L, with the concentrations of KOH and H2O2 both being 0.5 mol / L.

[0107] (2) Using a high-pressure pump, solution C, subcritical water, and additive C were simultaneously drawn into the reactor in the form of continuous sampling. The extraction flow rates were 20 mL / min, 40 mL / min, and 10 mL / min, respectively. The reactor was maintained at 350°C and 20 MPa and operated continuously. The three liquids were mixed and hydrolyzed in the reactor for 5 seconds to obtain a precursor suspension. After continuous extraction for 250 minutes, a suspension of high-entropy oxide precursor PE-A was formed, totaling 17.5 L.

[0108] (3) The suspension PE-A was spray-washed three times and then freeze-dried. The dried sample was rapidly annealed at 1000°C in a mixed atmosphere (40% O2 by volume, balance N2) with a heating rate of 100°C / s and a heat treatment time of 40s. After cooling, 55.73g of high entropy oxide was obtained, which was recorded as PE-A.

[0109] The product PE-A prepared in this example is a high entropy oxide La(Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 )O3, has a typical perovskite crystal structure, space group is Pm-3m, and no impurity phase is generated ( Figure 7 ).

[0110] The six metal elements La, Cr, Mn, Fe, Co, and Ni are evenly distributed in the sample, and the element ratio remains 5:1:1:1:1:1 ( Figure 8 ).

[0111] Example 4

[0112] (1) Prepare three 200 mL aqueous solutions of metal salts, respectively, and name them FL-A, FL-B, and FL-C. FL-A contains five metal salts: Ce(NO3)3, La(NO3)3, Pr(NO3)3, Sm(NO3)3, and Y(NO3)3; FL-B contains six metal salts: Ce(NO3)3, La(NO3)3, Pr(NO3)3, Sm(NO3)3, Y(NO3)3, and Nd(NO3)3; FL-C contains nine metal salts: Ce(NO3)3, La(NO3)3, Pr(NO3)3, Sm(NO3)3, Y(NO3)3, and Nd(NO3)3. r(NO3)3, Sm(NO3)3, Y(NO3)3, Nd(NO3)3, Gd(NO3)3, Ho(NO3)3, Er(NO3)3. In the above three systems, the concentration of each nitrate in each system is 0.01 mol / L; the total concentration of metal salts in FL-A is 0.05 mol / L, the total concentration of metal salts in FL-B is 0.06 mol / L, and the total concentration of metal salts in FL-C is 0.09 mol / L; oxalic acid is weighed and dissolved in deionized water to prepare auxiliary agent D with a concentration of 0.1 mol / L, a total of 600 mL;

[0113] (2) A high-pressure pump was used to simultaneously draw FL-A-series metal salt solution, subcritical water, and additive D into the reactor in the form of continuous sampling. The extraction flow rates were 7.5 mL / min, 37.5 mL / min, and 7.5 mL / min, respectively. The channel of the metal salt solution was equipped with an electronically controlled valve to achieve seamless switching between the injections of each sample. The reactor was maintained at 280°C and 22 MPa and operated continuously. The three liquids were mixed and hydrolyzed in the reactor for 30 seconds to obtain a precursor suspension.

[0114] After each FL solution injection, the next sample was sequentially switched to the next one for reaction. The corresponding suspension products were collected separately, numbered A through C, and named consistent with the solution. After continuous extraction for 80 minutes (26.67 minutes for each metal salt solution), 1.4 L of each suspension of the high-entropy oxide precursors FL-A, FL-B, and FL-C was formed.

[0115] (3) Three portions of FL-A suspension were washed three times simultaneously at a speed of 8000 r / min using a multi-channel high-speed centrifuge, and then freeze-dried using a vacuum dryer. The dried samples were subjected to high-throughput parallel rapid annealing treatment at 700°C in a mixed atmosphere (10% O2 by volume, the balance being N2) with a heating rate of 100°C / s and a heat treatment time of 50s. After cooling, three high-entropy oxides were obtained: FL-A, FL-B, and FL-C, with respective weights of 1.51g, 1.97g, and 2.89g.

[0116] The three products prepared in this example are all high entropy oxides with a single crystal structure, all of which are typical fluorite crystals with a space group of Fm-3m and no impurity phases ( Figure 9 ).

[0117] Under the microscopic view, all three samples are nanoparticles with a particle size distribution of 30-70nm ( Figure 10 All elements are evenly distributed in each sample ( Figure 11 ), and the element ratio is consistent with the ratio set when the solution is prepared. The samples are:

[0118] FL-A is (Ce 0.2 La 0.2 Pr 0.2 Sm 0.2 Y 0.2 )O2;

[0119] FL-B is (Ce 0.167 La 0.167 Pr 0.167 Sm 0.167 Y 0.167 Nd 0.167 )O2;

[0120] FL-C is (Ce 0.111 La 0.111 Pr 0.111 Sm 0.111 Y 0.111 Nd 0.111 Gd 0.111 Ho 0.111 Er 0.111 )O2.

[0121] Example 5

[0122] (1) Six soluble metal salts, Mg(NO3)2, CH3CH(O-)CO2NH4Ti(OH), Mn(NO3)2, Co(NO3)2, Ni(NO3)2, and Zn(NO3)2, were dissolved in deionized water at a molar ratio of 1:1:1:1:1:1 to prepare 1 L of solution SP-B, with the concentration of each metal ion being 0.02 mol / L. NaOH was weighed and dissolved in deionized water to prepare additive E, with a concentration of 1.0 mol / L, for a total of 1 L.

[0123] (2) A high-pressure pump was used to simultaneously extract the solution SP-B, subcritical water, and additive E into the reactor in the form of continuous sampling. The extraction flow rates were 30 mL / min, 90 mL / min, and 30 mL / min, respectively. The reactor was maintained at 360°C and 18 MPa and operated continuously. The three liquids were mixed and hydrolyzed in the reactor for 10 seconds to obtain a precursor suspension. After continuous extraction of the liquid for 33.3 minutes, a suspension of the high-entropy oxide precursor SP-B was formed, totaling 5 L.

[0124] (3) The suspension SP-B was washed three times by ultrasonic oscillation and then dried by infrared irradiation. The dried sample was rapidly annealed in an air atmosphere (20% O2 by volume, balance N2) at 1200°C with a heating rate of 120°C / s and a heat treatment time of 100s. After cooling, 8.98g of high entropy oxide was obtained, which was recorded as SP-B.

[0125] The product SP-B prepared in this example is a high entropy oxide (Mg 0.167 Ti 0.167 Mn 0.167 Co 0.167 Ni 0.167 Zn 0.167 )3O4, with spinel crystal form, space group Fd-3m, no impurity phase formation ( Figure 12 ).

[0126] The six metal elements Mg, Ti, Mn, Co, Ni, and Zn are evenly distributed in the sample, and the element ratio is maintained at 1:1:1:1:1:1. Under the microscopic microscope, SP-B is a nanoparticle with a particle size distribution of 50-70nm ( Figure 13 ).

[0127] Example 6

[0128] (1) Prepare three 500 mL aqueous solutions of metal salts, named RS-B, PE-B, and PY-A, respectively. RS-B contains six metal salts: LiNO3, Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, and Zn(NO3)2. The concentration of each metal salt in each aqueous solution is 0.01 mol / L, that is, the molar ratio of the six metal elements is 1:1:1:1:1:1;

[0129] In addition, PE-B contains six metal salts: Ce(NO3)3, La(NO3)3, Pr(NO3)3, Sm(NO3)3, Nd(NO3)3, and Mn(NO3)2; PY-A contains six metal salts: LaCl3, PrCl3, SmCl3, NdCl3, TbCl3, and SnCl4. The six elements are prepared in a molar ratio of 1:1:1:1:1:5, and the total concentration of metal elements in each metal salt aqueous solution is 0.1 mol / L; NH3·H2O is measured and diluted with deionized water to prepare additive F with a concentration of 1.0 mol / L, a total of 750 mL;

[0130] (2) A high-pressure pump is used to simultaneously draw metal salt solution, subcritical water, and additive F into the reactor in the form of continuous sampling. The extraction flow rates are 20 mL / min, 50 mL / min, and 10 mL / min, respectively. The channel of the metal salt solution is equipped with an electronically controlled valve to perform seamless switching between the injections of each sample. The reactor is maintained at 350°C and 22 MPa and continuously operated. The three liquids are mixed and hydrolyzed in the reactor for 30 seconds to obtain a precursor suspension.

[0131] After each solution injection, the next sample was switched to react in the order of RS-B, PE-B, and PY-A. The corresponding suspension products were collected separately and named consistent with the solutions. After continuous liquid extraction for a total of 75 minutes (25 minutes for each metal salt solution), 2 L of suspensions of high-entropy oxide precursors RS-B, PE-B, and PY-A were formed.

[0132] (3) The suspension was washed three times by multi-channel filter pressing and then freeze-dried. The dried sample was subjected to high-throughput parallel rapid annealing treatment in an air atmosphere (20% O2 and the balance N2 by volume) at 1000°C with a heating rate of 100°C / s and a heat treatment time of 120s. After cooling, three stable high-entropy oxides were obtained: RS-B, PE-B, and PY-A, with respective weights of 1.86g, 5.63g, and 7.28g.

[0133] The three products prepared in this example are all high entropy oxides with a single crystal structure and no impurity phase is generated ( Figure 14 ). Among them, all elements are evenly distributed in each sample, and the element ratio is consistent with the ratio set when the solution is prepared ( Figure 15 ), each sample is:

[0134] RS-B is (Li 0.167 Mg 0.167 Co 0.167 Ni 0.167 Cu 0.167 Zn 0.167)O, rock salt crystal form, space group Fm-3m;

[0135] PE-B is (Ce 0.2 La 0.2 Pr 0.2 Sm 0.2 Nd 0.2 )MnO2 is a perovskite crystal with space group Pm-3m,

[0136] PY-A is (La 0.2 Pr 0.2 Sm 0.2 Nd 0.2 Tb 0.2 )2Sn2O7 is a pyrochlore crystal type with a space group of Fd-3m.

[0137] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A continuous synthesis method of a high entropy oxide with controllable crystal form, components and proportions, comprising the following steps: A continuous sampling method is adopted to mix a soluble metal salt aqueous solution, subcritical water and an auxiliary agent, and a hydrolysis reaction is carried out to obtain a high entropy oxide precursor; the mixing temperature is 200 to 370° C. and the pressure is 15 to 22 MPa; The high entropy oxide precursor is subjected to rapid annealing treatment by a high-throughput processing method to obtain a high entropy oxide; The type of metal element in the soluble metal salt aqueous solution corresponds to a high entropy oxide of the same crystal form and the same elemental composition; Or the type of metal element in the soluble metal salt aqueous solution corresponds to a high entropy oxide of the same crystal form and different elemental composition; Or the types of metal elements in the soluble metal salt aqueous solution correspond to high entropy oxides of different crystal forms and different elemental components; The auxiliary agent includes an acid, a base or an oxidizing agent; The heating rate of the rapid annealing treatment is >80°C / s; the temperature of the rapid annealing treatment is 500-1400°C; the holding time of the rapid annealing treatment is 10-300s; in terms of volume fraction, the carrier gas of the rapid annealing treatment includes 5-100% O2, and the balance is N2; The high entropy oxide includes one or more of rock salt crystal type high entropy oxide, spinel crystal type high entropy oxide, fluorite crystal type high entropy oxide, perovskite crystal type high entropy oxide and pyrochlore crystal type high entropy oxide.

2. The continuous synthesis method according to claim 1, characterized in that The concentration of each metal ion in the soluble metal salt aqueous solution is independently 0.001 to 1 mol / L.

3. The continuous synthesis method according to claim 1, characterized in that The acid includes nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid or oxalic acid, the alkali includes ammonia water, sodium hydroxide or potassium hydroxide, the oxidant includes hydrogen peroxide, percarbonate or persulfate, and the concentration of the auxiliary agent is 0.1-10 mol / L.

4. The continuous synthesis method according to any one of claims 1 to 3, characterized in that: The volume ratio of the soluble metal salt aqueous solution, subcritical water and auxiliary agent is 1:2-5:0.1-1.

5. The continuous synthesis method according to claim 1, characterized in that The hydrolysis reaction time is 2 to 30 seconds.

6. The continuous synthesis method according to claim 1, characterized in that The general chemical formula of the rock salt crystal high entropy oxide is The lattice space group is Fm-3m, and the metal element R N Including 5 to 8 of Li, Na, Mg, Cr, Mn, Co, Ni, Cu, Zn, and Ga; the atomic ratio of each metal element Xn=0.111 to 0.333 and The general chemical formula of the spinel crystal high entropy oxide is The lattice space group is Fd-3m, and the metal element S N Including 5 to 9 of Li, Mg, Ca, Sr, Ba, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn and Al; the atomic ratio of each metal element Xn=0.100 to 0.333 and The chemical formula of the fluorite crystal type high entropy oxide is The lattice space group is Fm-3m or Ia-3m, and the metal element F N It includes 5 to 9 of Y, Zr, La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, and the atomic ratio of each metal element is Xn=0.100 to 0.333 and 7. The continuous synthesis method according to claim 1, characterized in that The general chemical formula of the perovskite crystal high entropy oxide is The lattice space group is Pm-3m, A K is the metal element contained in the A-site ion of the perovskite high entropy oxide. K Including K species among Ca, Sr, Ba, Y, La, Pr, Nd, Sm and Gd, 1≤K≤6; B M is the metal element contained in the B-site ion, B M M kinds of Ti, Cr, Mn, Fe, Co, Ni, Zn and Zr are included, 1≤M≤6, N=K+M and 6≤N≤10, the atomic ratios of metal elements Xk and Ym at the A position or B position are independently 0.143 to 1.000, and 8. The continuous synthesis method according to claim 1, characterized in that The chemical formula of the pyrochlore crystal type high entropy oxide is The lattice space group is Fd-3m, C K is the metal element contained in the C-site ion of the pyrochlore crystal high entropy oxide, C K Including K species among Y, La, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er and Yb, 1≤K≤6; D M is the metal element contained in the D-site ion, D M The invention comprises M kinds of Ti, Sn, Cr, Mn, Fe, Co, Ni, Zr and Ir, 1≤M≤6, N=K+M and 6≤N≤10, the atomic ratios of metal elements Xk and Ym at the C position or D position are independently 0.143 to 1.000, and

Citation Information

Patent Citations

  • Metal oxide solid solution, preparation and use thereof

    CN1791554A